2017
DOI: 10.5935/1415-2762.20170037
|View full text |Cite
|
Sign up to set email alerts
|

Family Vulnerability of Children With Special Needs of Multiple, Complex And Continuous Care

Abstract: RESUMOEsta pesquisa objetivou identificar a vulnerabilidade familiar das crianças com necessidades especiais de cuidados múltiplos, complexos e contínuos. Trata-se de estudo transversal, realizado com famílias de 68 crianças. Os dados foram coletados no período de junho a setembro de 2015, por meio de entrevistas realizadas no domicílio. Utilizou-se amostragem não probabilística por conveniência e os dados foram analisados por meio de estatística descritiva e correlação de Pearson. Todas as famílias apresentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 6 publications
(7 reference statements)
0
18
0
3
Order By: Relevance
“…18 The issue of social support related to information is commonly addressed in the literature, especially with regard to the role of Nursing in providing information, clarifying doubts and offering permanent support to the families of CRIANES. 4,5,11,12 In this sense, nurses are seen as educators both in the hospital and in primary care 4 and have the potential to become sources of social support, as they promote comprehensive and resolute care through informative, instrumental and emotional assistance. 12 However, the discontent of family members of children who need continuous and complex care is still common, complaining that they have not been adequately prepared to perform care after discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The issue of social support related to information is commonly addressed in the literature, especially with regard to the role of Nursing in providing information, clarifying doubts and offering permanent support to the families of CRIANES. 4,5,11,12 In this sense, nurses are seen as educators both in the hospital and in primary care 4 and have the potential to become sources of social support, as they promote comprehensive and resolute care through informative, instrumental and emotional assistance. 12 However, the discontent of family members of children who need continuous and complex care is still common, complaining that they have not been adequately prepared to perform care after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…2 They are considered as a subgroup of children with special health needs (CRIANES). [2][3][4] Caring for a child who requires continuous and complex care implies the need for family rearrangements to meet the intense care routine, 5 leading to family breakdown 3,6 and overload of the main caregiver, usually mothers. 7 To this end, the importance of the social network and social support in coping with this reality is reinforced.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, evidencia-se que as crianças com condições crônicas, em especial aquelas com necessidades especiais de cuidados múltiplos, complexos e contínuos, estão em situação de vulnerabilidade programática 16 . Assim, a fragilidade na articulação entre os diferentes níveis e locais de prestação de serviços impacta diretamente no retorno da criança ao território e na qualidade da assistência que será prestada a ela e à família, assim como da referência e contrarreferência nos variados graus de complexidade, por vezes ineficaz e pouco empregada 17 .…”
Section: Discussionunclassified
“…One of the experiences took place in a study carried out in Maringá-PR (6) , in which the researchers contacted all nurses or coordinators of the 29 Basic Health Units ( BHU) in the city and, also, informal conversation with community health workers(CHW) of the 62 FHS teams. At this time, they requested the indication of children residing in the area covered by the Unit who would be able to be included in the study because they have special needs for continuous/complex care.…”
Section: Strategies To Identify Children With Special Health Needs In Primary Carementioning
confidence: 99%
“…Likewise, the study carried out in Maringá found that of the 68 participating CSHN, 40 were not visited by any member of the FHS team, 21 were visited only by the CHW and only seven reported that they were, in fact, followed-up by the FHS team. Also, the reports showed that in the face of some health problems, the child was not considered a priority when scheduling medical appointments, raising the need to seek emergency care services and/or even hire private health insurance (6) .…”
Section: The Experience Of Families Concerning Phc Servicesmentioning
confidence: 99%